2008
DOI: 10.1121/1.2828064
|View full text |Cite
|
Sign up to set email alerts
|

Inverted direction of wave propagation (IDWP) in the cochlea

Abstract: The "classical" view on wave propagation is that propagating waves are possible in both directions along the length of the basilar membrane and that they have identical properties. Results of several recently executed experiments [T. Ren, Nat. Neurosci. 2, 333-334 (2004) and W. X. He, A. L. Nuttall, and T. Ren, Hear. Res., 228, 112-122 (2007)] appear to contradict this view. In the current work measurements were made of the velocity of the guinea-pig basilar membrane (BM). Distortion products (DPs) were produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 33 publications
(31 reference statements)
4
33
0
Order By: Relevance
“…The modeling studies reported here address the counterintuitive experimental finding (Ren, 2002;He et al, 2007He et al, , 2008He et al, , 2010de Boer and Nuttall, 2008) that the spatial phase profile of the DP traveling wave along the BM has a negative phase slope (NPS), implying that DP waves are traveling predominantly into the cochlea rather than out of it. The explanation proposed by Ren is that backwardtraveling waves on the BM are small (or nonexistent) because the DP energy escapes from the cochlea via an alternative propagation mode (namely fast compressional waves in the fluid) that, unlike the transpartition pressure wave, couples only weakly (if at all) to the motion of the BM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The modeling studies reported here address the counterintuitive experimental finding (Ren, 2002;He et al, 2007He et al, , 2008He et al, , 2010de Boer and Nuttall, 2008) that the spatial phase profile of the DP traveling wave along the BM has a negative phase slope (NPS), implying that DP waves are traveling predominantly into the cochlea rather than out of it. The explanation proposed by Ren is that backwardtraveling waves on the BM are small (or nonexistent) because the DP energy escapes from the cochlea via an alternative propagation mode (namely fast compressional waves in the fluid) that, unlike the transpartition pressure wave, couples only weakly (if at all) to the motion of the BM.…”
Section: Discussionmentioning
confidence: 99%
“…The basic assumption of de Boer et al (2008) was that a backward wave, propagating from the DP generation place, either x 2 or x DP , to the cochlear base should have a PPS at a fixed place, x 0 . We have seen that this assumption can be justified by the arguments leading to Eq.…”
Section: A Frequency-domain Analytical Estimatesmentioning
confidence: 99%
See 1 more Smart Citation
“…One reason is that most of the studies have focused on frequency regions around the BF, which seem to be dominated by the local/forwardtraveling component, especially for the 2f 1 − f 2 [see DP evoked by 50 dB SPL, blue lines in Fig. 2 and, i.e., Ren (2004) andde Boer et al (2008)]. When an effort was made to make the comparison between the DPs measured at two longitudinal BM locations, the ∼200 μm separation of two locations appeared to not be large enough to resolve the non-local reversetraveling component when considering that the generation region broadens with increasing primary levels (He et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of DPs are complex when measured at one location in the cochlea and appear to include both local and non-local or forward-and reverse-traveling components (de Boer 2007;de Boer et al 2007;Rhode 2007;Shera et al 2007;de Boer et al 2008;Dong andOlson 2008, 2010). Therefore, recognizing different components of the measured intracochlear DP is an important starting point.…”
Section: Propagation Of Dps In the Cochleamentioning
confidence: 99%